2021
DOI: 10.1016/j.adro.2021.100761
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Spleen as an Organ at Risk in Radiation Therapy and Its Relationship With Radiation-Induced Lymphopenia: A Retrospective Study and Literature Review

Abstract: Purpose We conducted a systematic review and a retrospective study to investigate the relationship between spleen irradiation and lymphocyte toxicity. Methods and Materials Forty-six patients diagnosed with locally advanced gastric, esophageal, and pancreatic cancer who underwent radiation therapy were included in this study. The spleen was contoured for each patient. Volumes that received 5 up to 40 Gy (5 Gy increments), minimum, mean, and maximum dose were considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…However, there might be more organs to account for, such as the spleen. A study showed that higher splenic dose increases the risk of lymphopenia in a series of upper abdominal cancers, including EC [ 47 , 48 ]. Saito et al showed that when the mean splenic dose increased by 1 Gy, the predicted ALC decreased by 2.9% in EC patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there might be more organs to account for, such as the spleen. A study showed that higher splenic dose increases the risk of lymphopenia in a series of upper abdominal cancers, including EC [ 47 , 48 ]. Saito et al showed that when the mean splenic dose increased by 1 Gy, the predicted ALC decreased by 2.9% in EC patients [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genome-wide association studies [ 34 , 35 , 36 ] failed to link ABO blood groups to NPC risk. It is already widely accepted that lymphocyte counts are important prognostic factors for cancer patients [ 37 , 38 , 39 , 40 ]. The study of Zhang Y et al [ 32 ] is the only one to evaluate the link between the ABO blood group, tumor stage and blood lymphocyte counts.…”
Section: Discussionmentioning
confidence: 99%
“…One other possible mechanism might involve surgical stress, which could promote contamination of microbiota with skin bacteria and lead to the disruption of the local T lymphocytes, thus creating an increased risk of SSI [56,62,63].…”
Section: Infectious Complicationsmentioning
confidence: 99%